2021
DOI: 10.1177/11207000211041975
|View full text |Cite
|
Sign up to set email alerts
|

Time for return to sport following total hip arthroplasty: a meta-analysis

Abstract: Introduction: Total Hip Arthroplasty (THA) is being increasingly undertaken in younger and more active patients, with many of these patients wanting to return to sport (RTS) after surgery. However, the percentage of patients RTS and time at which they are able to get back to sport following surgery remains unknown. The objective of this meta-analysis was to determine the time patients RTS after THA. Methods: A search was performed on PUBMED, MEDLINE, EMBASE, and the Cochrane Library for trials on THA and RTS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This knowledge is crucial for both physicians and patients to understand the potential impact on an active lifestyle. However, the reported data are lower compared to the rates of RTS after elective hip arthroplasty in a middle-aged population [44].…”
Section: Discussionmentioning
confidence: 75%
“…This knowledge is crucial for both physicians and patients to understand the potential impact on an active lifestyle. However, the reported data are lower compared to the rates of RTS after elective hip arthroplasty in a middle-aged population [44].…”
Section: Discussionmentioning
confidence: 75%
“…A recent meta-analysis by Magan et al 13 investigated return to sports after THA. From 11 eligible studies on 2297 patients, the authors reported an overall adjusted return-to-sports rate of 84% (95% CI, 71%-94%) at the end of the follow-up period, which ranged between 4 and 48 months.…”
Section: Discussionmentioning
confidence: 99%
“…Although these things are necessary for basic activities of daily living, young, active patients expect to be able to do far more than these basic activities of daily living. Patients commonly expect to return to sports [9], in some cases at an elite level [10], return to various types of paid labor, be able to socialize more [5], and improve their mental health and sexual functioning [8], as well as other activities that are not generally measured by existing PROMs.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%